Implikasi Motivasi Kerja dan Iklim Organisasi Terhadap Kepuasan Kerja di Era Pandemi Covid-19 - Yuri Rahayu; Galih Raspati; Andi Riyanto (Yayasan Literasi Sains Indonesia, 2022)
Human Resources (HR) is important in an organization, especially for profit-oriented business entities. The role of skilled, creative and innovative human resources can make it easier for the company to achieve its vision and mission. Companies not only need employees who are reliable in their performance, but also need those who are loyal to do more for the company and don't leave the Company in the midst of uncertainty during this pandemic, but in fact many employees are unable to deal with this, thus affecting their overall performance. The method used is quantitative because it relates to the number of survey results. With the research stage conducting a preliminary study by starting to know the problem, literature review, previous research studies, field studies, descriptions and analysis of findings. The results showed that the T-Test of Work Motivation Variables (X1) had a positive and significant influence on the Employee's Work Climate (Y), the T-Test Results for Variables (X2) had a positive and significant effect on employee activities (Y) and the results of the F table test ( Farsial) it was found that the variables of Work Motivation (X1) and Organizational Climate (X2) had a positive and significant effect simultaneously on the work activities of employees (Y) in the production division of PT. Build Baros Cempaka Sukabumi.